NATURAL AND PREMATURE PHYSICAL FACTORS IN TREATMENT OF HORMONE-DEPENDENT DISEASES OF FEMALE REPRODUCTIVE SYSTEM - S. A. Kurilenok; V. A. Krutova; O. V. Avagimova; K. V. Gordon (Кубанский научный медицинский вестник)
Hormone-dependent diseases of the female reproductive system is often accompanied by the clinical course of chronic inflammatory diseases of female pelvic organs that are often difficult to use natural and preformed physical therapeutic factors during the period of this group of patients with gynecological spa treatment . Rehabilitation technologies and  treatment of this group of gynecological patients at a sanatorium stage may include methods such as iodine and bromine and radon balneotherapy, ozone therapy, EHF-therapy and transcranial electrical stimulation, therapeutic and prophylactic efficacy and safety results of which are demonstrated in this study.